Bias Gender Pemberitaan Kasus Gisella Anastasia di Okezone.com - Stara Asrita (Jurnal Komunikasi Nusantara, 2022)
Gender bias against women is still common in media coverage. The news of Gisella Anastasia's arrest because of pornographic video news was quite busy being discussed in online media. In her reporting, Gisella tends to be used as an object of discrimination. This study aims to determine the form of sexism in okezone.com's coverage of the Gisella Anastasia case. A qualitative approach is used in this study to fit Sara Mills' critical discourse analysis. Sara Mills focuses on looking at the hidden meanings of biased texts related to women's reporting. Critical discourse analysis examines how the representation of the actor's position through the text, how the position of the reader is represented in the text. Through discourse, researchers can analyze the factors of production and acceptance. The results of the study show that the position of news-producing actors are male and female journalists, while Gisella Anastasia is a woman who is used as a sexual object. News writers tend to provide news to satisfy men's sexual desires by raising the issue of sexism. The gender bias in the reporting of the Gisella Anastasia case is related to sexist language, images that are considered lustful, and the point of view of journalists who have a patriarchal ideology. Abstrak Bias gender terhadap perempuan adalah hal yang masih sering terjadi dalam liputan media. Pemberitaan penangkapan Gisella Anastasia karena berita video porno cukup ramai diperbincangkan di media daring. Dalam pemberitaannya, Gisella cenderung dijadikan sebagai objek yang mengalami diskriminasi. Penelitian ini bertujuan untuk mengetahui bentuk seksisme dalam liputan okezone.com atas kasus Gisella Anastasia. Pendekatan penelitian kualitatif digunakan dsecara deskriptif agar sesuai model Sara Mills. Sara Mills berfokus untuk melihat makna tersembunyi pada teks bias yang berhubungan dengan pemberitaan perempuan. Analisis wacana kritis mengkaji bagaimana representasi posisi aktor melalui teks, bagaimana posisi pembaca direpresentasikan dalam teks. Melalui wacana, peneliti dapat menganalisis faktor produksi dan penerimaannya. Hasil dari penelitian memperlihatkan bahwa posisi aktor penghasil berita adalah jurnalis laki-laki dan perempuan, sedangkan Gisella Anastasia adalah perempuan yang dijadikan sebagai objek seksual. Penulis berita cenderung memberikan berita untuk memuaskan hasrat seksual laki-laki dengan mengangkat isu seksisme. Bias gender dalam kasus pemberitaan kasus Gisella Anastasia terkait dengan bahasa yang seksis, gambar yang dianggap mengundang nafsu, serta sudut pandang jurnalis yang memiliki ideologi patriarki.